A multiprofessional information model for Brazilian primary care: Defining a consensus model towards an interoperable electronic health record. (June 2016) - ,; Lucena, Fábio Nogueira de; Ribeiro-Rotta, Rejane Faria; Braga, Renata Dutra
Abstract: Objective: To develop a multiprofessional information model to be used in the decision-making process in primary care in Brazil. Methods: This was an observational study with a descriptive and exploratory approach, using action research associated with the Delphi method. A group of 13 health professionals made up a panel of experts that, through individual and group meetings, drew up a preliminary health information records model. The questionnaire used to validate this model included four questions based on a Likert scale. These questions evaluated the completeness and relevance of information on each of the four pillars that composed the model. The changes suggested in each round of evaluation were included when accepted by the majority (≥ 50%). This process was repeated as many times as necessary to obtain the desirable and recommended consensus level (> 50%), and the final version became the consensus model. Results: Multidisciplinary health training of the panel of experts allowed a consensus model to be obtained based on four categories of health information, called pillars: Data Collection, Diagnosis, Care Plan and Evaluation. Conclusion: The obtained consensus model was considered valid by the experts and can contribute to the collection and recording of multidisciplinary information in primary care, as well as the identification of relevant concepts for defining electronic health records at this level of complexity in health care.